Reinforcing effects of fentanyl analogs found in illicit drug markets - Alexander D. Maitland; Shelby A. McGriff; Grant C. Glatfelter; Charles W. Schindler; Michael H. Baumann (Psychopharmacology, 2024)
Rationale The potent synthetic opioid fentanyl, and its analogs, continue to drive opioid-related overdoses. Although the pharmacology of fentanyl is well characterized, there is little information about the reinforcing effects of clandestine fentanyl analogs (FAs). Objectives Here, we compared the effects of fentanyl and the FAs acetylfentanyl, butyrylfentanyl, and cyclopropylfentanyl on drug self-administration in male and female rats. These FAs feature chemical modifications at the carbonyl moiety of the fentanyl scaffold. Methods Sprague-Dawley rats fitted with intravenous jugular catheters were placed in chambers containing two nose poke holes. Active nose poke responses resulted in drug delivery (0.2 mL) over 2 s on a fixed-ratio 1 schedule, followed by a 20 s timeout. Acquisition doses were 0.01 mg/kg/inj for fentanyl and cyclopropylfentanyl, and 0.03 mg/kg/inj for acetylfentanyl and butyrylfentanyl. After 10 days of acquisition, dose-effect testing was carried out, followed by 10 days of saline extinction. Results Self-administration of fentanyl and FAs was acquired by both male and female rats, with no sex differences in acquisition rate. Fentanyl and FAs showed partial inverted-U dose-effect functions; cyclopropylfentanyl and fentanyl had similar potency, while acetylfentanyl and butyrylfentanyl were less potent. Maximal response rates were similar across drugs, with fentanyl and cyclopropylfentanyl showing maximum responding at 0.001 mg/kg/inj, acetylfentanyl at 0.01 mg/kg/inj, and butyrylfentanyl at 0.003 mg/kg/inj. No sex differences were detected for drug potency, efficacy, or rates of extinction. Conclusions Our work provides new evidence that FAs display significant abuse liability in male and female rats, which suggests the potential for compulsive use in humans.